CALCULADORA METANALÍTICA: SOFTWARE PARA METANÁLISE BAYESIANA DE PROPORÇÕES - GOMES, Letícia Souza; DE CAMPOS, Adriano Polpo; PEREIRA, Carlos Alberto de Bragança; MARTINS, Camila Bertini (Brazilian Journal of Biometrics, 2019)
Due to the relevance of the use of systematic review and meta-analysis techniques in the acquisition of consistent and reliable information in the different areas of knowledge, this paper presents a preliminary version 1.0.0 of the Calculadora Metanalítica software, developed in languages R and C #, with graphical interface of use, which perform a Bayesian meta-analysis of proportions. The software allows the user to enter the study weights, if desired. In addition to the graph resulting from the meta-analysis, a text file can also be saved that allows completing complements. The steps for installing and using the program are described here. For application of the software is a solution for the prevalence of depressive symptoms in Brazilian elderly hospitalized in health units of Brazil. At the end, some considerations of the use of the Calculadora Metanalítica are presented.